Numerical investigation and optimization of liquid battery thermal management system considering nanofluids, structural, and flow modifications under high discharge cycles - Abdelrahman Gasmelseed; Mhadi A. Ismael; Mior A. Said; Faiz Ahmad (Case Studies in Thermal Engineering)
The thermal management of electric vehicle (EV) batteries continues to be a pressing challenge preventing wider EV adoption due to performance and safety concerns. Liquid battery thermal management systems (BTMSs) are the most commercially viable thermal management option due to their high heat transfer efficiency and compact design, despite these promising features, the current liquid BTMS designs suffer from high energy consumption and temperature gradients which severely affect the BTMS performance. To address these issues, this study numerically investigated the influence of various liquid BTMS design parameters for a 12 cylindrical lithium-ion battery module. The study evaluated 21 different BTMS configurations based on the maximum battery temperature, temperature difference, pressure drop, and energy consumption. Based on the selected evaluation criteria, The optimized liquid BTMS design (one cooling block, bidirectional flow, 0.0015 kg/s mass flow rate, 4 mm cell spacing, continuous operation strategy with hybrid CuO-MgO-TiO2 water 0.5 % concentration nanofluid) maintained the maximum temperature and temperature difference at 31.34 and 5.3 °C respectively, a 4.3 % and 21.1 % improvement compared to the base design, with a total pressure drop of 12.84 Pa when operated under 35 °C ambient temperature and 3C discharge rate. Proving the effectiveness of the proposed liquid BTMS design.